Development of the Tirta Sumber Jaya Cipangalun Tourism Object in Increasing Village Community Income: A Study of Islamic Economic Perspectives - Nurlativah, Ai; Sumarni, Sumarni; Agung, Ahmad; Aminullah, Rifqi Arief (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, INDONESIA, 2023)
This study aims to analyze the contribution of the development of Tirta Sumber Jaya tourist attraction in increasing the income of the people of Jalatrang Village, Cipaku Subdistrict, Ciamis Regency, especially from the perspective of Islamic economics. The results showed that the tourism activities carried out in the Tirta Sumber Jaya Cipangalun Tourist Attraction in Jalatrang Village, Cipaku Subdistrict, Ciamis Regency, both service activities to visitors, management activities and relationship activities with the surrounding community are in accordance with the principles of Islamic economics. The existence of the construction of Tirta Sumber Jaya Cipangalun Tourist Attraction provides a positive change (increase) in the income of the people of Jalatrang Village, Cipaku Subdistrict, Ciamis Regency. The contribution of the development of Tirta Sumber Jaya Cipangalun Tourist Attraction in increasing the income of the people of Jalatrang Village, Cipaku Subdistrict, Ciamis Regency occurs through the opening of employment opportunities both as employees of the tourist attraction and as traders in the tourist attraction area and the growth of community business centers along the road to Tirta Sumber Jaya Cipangalun Tourist Attraction.